Mapping Needs: Designing English Module For Tourism And Hotel (Emth) - Dina Syarifah Nasution; Syahrul R; Mukhaiyar (RETORIKA: Jurnal Ilmu Bahasa, 2023)
This research aimed to identify the learning and target needs, as well as the importance of English for students in the tourism and hotel industry. Utilizing a survey method, data was collected through questionnaires and interviews with students and professionals in the hospitality sector. Listening emerged as the skill of highest priority at 83.33%, while Speaking and Reading were equally critical at 91.67%. Surprisingly, Writing was designated as High Needed at 66.67%, highlighting a pressing need for enhanced written communication. Additionally, the study revealed that "Greeting" was classified as â€œThe Highest Neededâ€ at 82.86%, emphasizing its crucial role in guest interactions. "Asking and giving information" (91.43%) and "Offering services" (77.14%) were identified as essential for providing quality service and ensuring customer satisfaction. Strong language proficiency is imperative in various areas, including â€œHotel facilities,â€ â€œHotel and restaurant services,â€ â€œPhone calls complaints and solutions,â€ â€œWriting email & responding to email to customers,â€ and â€œReading travel books, hotel documents, brochures,â€ all categorized as â€œThe Highest Neededâ€ (77.14% to 85.71%). Notably, â€œReservation and check-inâ€ and â€œTransportationâ€ were classified as â€œHigh Neededâ€ at 71.43%, signifying their importance although not reaching the highest level of necessity in the industry.